Age-independence for media pedagogy - Haubold, Rebekka (Array, 2020)
Age is a static socio-demographic dimension, but is it still a useful category for media pedagogy and media competencies? This article is a theoretical examination of the fixation on age in German media pedagogy research and practice. The thesis of this article, therefore, is that this dominant focus on age should be shifted to neglected contexts and ways to discover them. The key point is to distinguish cases in which it makes sense to focus on age groups in media pedagogical research and practice from those in which it is discriminatory and less important than other factors. Therefore, it analyses historical developments that justified concentration on the subject in German media pedagogy and, thus, the overemphasis on age concepts.